Giant lipoma of the buccal fat pad: case report and literature review - Chang Yung Chia; Diego Antonio Rovaris; Rodrigo Fontana (Revista Brasileira de Cirurgia Plástica)
INTRODUCTION: Lipomas are the most common benign mesenchymal tumors. Nevertheless, they are infrequent in the face, particularly giant lipomas, which are derived from the buccal fat pad. The literature regarding these tumors is scarce and their incidence is likely underestimated. METHODS: We present a case report of surgical treatment of a relapsed giant buccal and temporal lipoma and review the related English literature in Pubmed and that in the Brazilian Journal of Plastic Surgery. RESULTS: The tumor, which anatomically and morphologically corresponded to the buccal fat pad, was completely excised by facial and temporal access without sequelae to the facial nerve. A total of 31 reported cases of lipoma originating from the buccal fat pad were found; however, several were found and reported under other names. DISCUSSION: The buccal fat pad is larger and more complex than assumed, and several pathologies are derived thereof, making the differential diagnosis of simple lipoma with fusiform cell lipoma and liposarcoma difficult due to their extreme similarities. CONCLUSION: In lipomatous lesions of the face, the possible origin in the buccal fat pad must be considered. An extensive study of these lesions with the purpose of standardizing the terminology and determining its real incidence must be performed.